2010
DOI: 10.1111/j.1467-9507.2009.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Support from Parents, Friends, Classmates, and Teachers in Children and Adolescents Aged 9 to 18 Years: Who Is Perceived as Most Supportive?

Abstract: Age and gender differences in perceived social support from parents, friends, classmates, and teachers were investigated in 304 boys and 351 girls aged 9-18 years. The social support scale for children and adolescents was used for this purpose. Analyses showed that the level of perceived social support from parents and friends was similar across age groups. The study of the prominence of social support sources showed that parents and friends were perceived as equally supportive; only for the ages 16-18 years d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
312
10
18

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(363 citation statements)
references
References 20 publications
23
312
10
18
Order By: Relevance
“…Boys reported a higher degree of participation in the classroom and greater teacher support, in contrast to the findings of Bokhorst et al . [42], who found that girls had more teacher support than boys. One explanation of why the present study shows a contradictory result might have to do with the way the variable was measured.…”
Section: Discussionmentioning
confidence: 99%
“…Boys reported a higher degree of participation in the classroom and greater teacher support, in contrast to the findings of Bokhorst et al . [42], who found that girls had more teacher support than boys. One explanation of why the present study shows a contradictory result might have to do with the way the variable was measured.…”
Section: Discussionmentioning
confidence: 99%
“…Por todo lo anterior, diversos estudios concluyen que el apoyo social percibido por los estudiantes puede reducir el efecto negativo de la victimización entre pares (Zhang et al, 2012). En esta misma línea, existen investigaciones que han demostrado el impacto de padres, amigos, profesores y compañeros de clase sobre las conductas conflictivas y desajuste escolar, en favor del desarrollo positivo de los adolescentes (Bokhorst, Sumter & Westenberg, 2010;Demaray & Malecki, 2002;Moreno Ruiz, Estévez López, Murgui Pérez & Musitu Ochoa, 2009), confirmando el impacto del apoyo social en las conductas individuales y grupales.…”
Section: Apoyo Social Y Victimización Entre Paresunclassified
“…Friends in particular are an important source of social support for many adolescents (e.g., Bokhorst, Sumter, & Westenberg, 2010) and increasingly gain importance during adolescence (e.g., Scholte & Van Aken, 2006). However, for contemporary youth, the notion of perceived friend support may have changed, due to the emergence and widespread use of SNSs.…”
Section: Active Facebook Use -Perceived Online Social Support -Depresmentioning
confidence: 99%